Assessment of resistance to permanent deformations of asphalt mixes of low air void content - Radziszewski Piotr; Sarnowski Michał; Pokorski Piotr (Open Engineering, 2021)
This article presents the issue of resistance to permanent deformations of bridge pavements. In Europe, bridge asphalt pavement usually consists of the wearing course and the protective layer, which are paved on the waterproofing. Protective layers of bridge pavement are often constructed using low air void asphalt mixes. Such mixes are characterized by water-tightness, resistance to unfavorable environmental conditions, and enhanced fatigue life. Due to increased binder content, asphalt mixes for bridge pavement may display reduced resistance to permanent deformations. The article presents the test results of resistance to permanent deformations of asphalt mixes for bridge pavement. The study compares the rutting resistance for mixture use with low air void content. This specific kind of mixtures are dedicated to pavements on bridge deck. In this study, the resistance to permanent deformations was tested depending on the content of grit structure and air void content. Laboratory test results were compared for stone mastic asphalt and asphalt concrete, characterized by low air void content. Resistance to permanent deformations was assessed using the cyclic uniaxial compression (dynamic load creep) method. On the basis of analysis of the test results, it was shown that resistance of asphalt mixes to permanent deformations depends most of all on the type of mix designed and the air void content.